2013
DOI: 10.1121/1.4820897
|View full text |Cite
|
Sign up to set email alerts
|

The salience of enhanced components within inharmonic complexes

Abstract: A subjective listening task was used to measure the salience of enhanced components using typical intensity-enhancement stimuli, time-reversed versions of those stimuli, and stimuli which contained a frequency shift of the target component. Twenty-five listeners judged whether or not a pitch "stood out" within an inharmonic complex. For comparison, judgments also were made for stimuli with a single segment that consisted of a simultaneously masked target. The results indicate that the perceived salience of enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…The maximal enhancement observed in Experiment 1 was over 24 dB on average, which is much larger than the 5–10 dB enhancement typically reported in many two-interval tasks if the sound intensity of maskers, precursor duration and gap duration are comparable (Viemeister, 1980). The size of enhancement in our study is comparable with that found by Byrne et al (2013) where participants reported the “pop-out” of the target tone, although the authors proposed that the larger enhancement was due to the reduction of informational masking. Indeed, in the no-precursor condition in our study, the individual thresholds varied from −10 dB to 29 dB TMR.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The maximal enhancement observed in Experiment 1 was over 24 dB on average, which is much larger than the 5–10 dB enhancement typically reported in many two-interval tasks if the sound intensity of maskers, precursor duration and gap duration are comparable (Viemeister, 1980). The size of enhancement in our study is comparable with that found by Byrne et al (2013) where participants reported the “pop-out” of the target tone, although the authors proposed that the larger enhancement was due to the reduction of informational masking. Indeed, in the no-precursor condition in our study, the individual thresholds varied from −10 dB to 29 dB TMR.…”
Section: Discussionsupporting
confidence: 87%
“…A study by Carcagno et al (2012) showed different time courses for ipsilateral and contralateral enhancement: enhancement decayed more rapidly for ipsilateral precursors, again suggesting multiple sources for enhancement. Different task designs and stimulus parameters could engage different sources, which might explain some of the discrepancy in the findings of previous studies, such as the effect of perceptual similarity between precursor and masker (Byrne et al., 2013; Carcagno et al, 2013; Carlyon, 1989; Summerfield et al, 1987; Viemeister et al, 2013) or the enhancement from a contralateral precursor (Carlyon, 1989; Erviti et al, 2011; Kidd et al, 2011; Richards et al., 2004; Summerfield et al, 1984; Viemeister, 1980). …”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…When the masker and target are later presented, the response to the target is enhanced since it is subjected to less suppression/inhibition. Recent findings have suggested that sensory mechanisms may be insufficient to fully account for the enhancement effect (e.g., Byrne et al, 2013). Rather, the benefit of the precursor may partially occur because it provides knowledge about the spectral content of the masker (Neff and Green, 1987; Richards and Neff, 2004; Richards et al, 2004; Kidd et al, 2011).…”
Section: Introductionmentioning
confidence: 99%